Attacking stressed pseudomonas aeriginosa with Wi-Fi - Sim, Nicholas Yi Ming (2017)
The effects of exposure to Wi-Fi radiation on Pseudomonas Aeruginosa was investigated. With the use of statistics, exposure to electromagnetic radiation significantly influenced the growth of planktonic cells adversely but not the biofilm when compared to its control. This is due to the Extracellular polymeric substance matrix which biofilm produces, it acts as a radiation-protective layer for its cells. The effects of divalent ions were investigated; Mg^(2+) is a function of PA-01’s growth. Next, the effect of both Ca^(2+) and Mg^(2+) on PA-01 were investigated. Interestingly, with increasing amounts of Ca&Mg (in the ratio of 1:1), glucose consumption stayed at a plateau until 12.5mM/L then it increased to a maximum point, suggesting that minimal glucose was consumed with low concentrations of Mg&Ca. Since divalent ions have an antagonistic competitive relationship, our results suggest that Ca^(2+) may be the preferred divalent ion uptake by PA-01 when concentration of Mg&Ca is low; which influences and exhibits minimal growth characteristics.